Sumber Daya dan Strategi Inovasi dalam Kewirausahaan : Analisis Sistematis dengan Metode Systematic Literature Review (SLR) - Feri Andika Prasetya; Kevin Ghulaman Silmi; Agung Winarno; Wening Patmi Rahayu (Global Leadership Organizational Research in Management, 2025)
Innovation is a key element in improving business competitiveness and sustainability. This study uses the Systematic Literature Review (SLR) method to analyse the relationship between resources and innovation strategies in entrepreneurship. A total of 22 Scopus-indexed articles were reviewed using the PRISMA approach, focusing on the types of resources (human, financial, technological, informational, and physical) and forms of innovation (product, process, and managerial). The results show that product innovation is largely supported by human resources and technology, where the skills and creativity of the workforce play an important role in the development of new products. Process innovation relies on technology and information, especially in production efficiency and operational digitalisation. Meanwhile, managerial innovation is closely related to human resource management and organisational strategy, which enables companies to be more adaptive to market changes. This study enriches the Resource-Based View (RBV) and Dynamic Capabilities theories, and provides insights for entrepreneurs and policy makers in developing resource-based innovation strategies. In conclusion, successful innovation in entrepreneurship depends on optimal resource utilisation and appropriate policy support to create sustainable innovation.